Chemical composition and toxicity of eucalyptus essential oil on spotted spider mite - Souza, Lauana Pellanda de; ZAGO, HUGO BOLSONI; Pinheiro, Patrícia Fontes; Valbon, Wilson Rodrigues; Zuim, Vitor; Pratissoli, Dirceu (Comunicata Scientiae, 2017)
The spotted spider mite, Tetranychus urticae Koch, 1836 (Acari: Tetranychidae) is a polyphagous pest which causes extensive damage to Brazilian agriculture. The control of this pest is usually performed by synthetic origin products. Thus, the essential oils with acaricide property can be resources considered as an alternative to control this pest. The objective of this study was to identify the chemical composition and evaluate the fumigation toxicity of Eucalyptus citriodora (Hook.) KD Hill & LAS Johnson essential oil on T. urticae. The essential oil extraction was performed by hydrodistillation, usinga Clevenger type apparatus . The compounds identification was made comparing the obtained mass spectra with the available spectra in the database of the spectral library Willey 330,000 and by the Kovats index (IK), calculated for each compound. Adult female spotted spider mite were subjected to doses of 3.57, 7.14, 10.71, 14.28 and 17.85 μL L-1 of the essential oil air in fumigation chambers during 24, 48 and 72 hours. Subsequently, lethal concentration (LC50) of the essential oil was estimated. Ten compounds were identified, being the citronellal (68.20%) the major compound. The LC50 value observed after 24, 48 and 72 hours of exposure to essential oil were 17.55, 17.00 and 10.50 μL L-1 of air, respectively, and the fecundity of T. urticae females reduced with an increase of the used concentrations.